Improving Antibiotic Use in Argentine Pediatric Hospitals: A Process Evaluation Using Normalization Process Theory - Roberti, Javier Eugenio (2025)
Introduction: In the pediatric setting, overprescribing of antibiotics contributes to the rise of multidrug-resistant organisms. Antimicrobial stewardship programs (ASPs) are recommended to optimize antibiotic use and combat resistance. However, the implementation of ASPs in low- and middle-income countries faces several challenges. This study aimed to evaluate the implementation process of a multifaceted ASP in 2 pediatric hospitals in Argentina.Methods: A qualitative study was conducted in two large public children’s hospitals in Argentina, using semistructured interviews with 32 healthcare providers at the beginning and end of the ASP implementation. The study was guided by the normalization process theory.Results: The intervention faced challenges, including limited understanding of its objectives, confusion with existing practices, and insufficient commitment from senior staff. Although junior staff were more receptive, communication barriers with external staff and workload concerns hindered broader adoption. Infectious disease specialists primarily led implementation, with limited involvement of other staff, particularly in training activities. Despite these challenges, participants reported improvements, such as the development of standardized antibiotic guidelines, better interdisciplinary collaboration, and improved communication. However, organizational support and resistance to new practices remained barriers.Conclusions: This study highlights the importance of organizational context and staff commitment in ASP implementation. Tailored strategies that address the specific challenges of low- and middle-income countries are needed to effectively implement ASPs.